2012
DOI: 10.2196/jmir.1976
|View full text |Cite
|
Sign up to set email alerts
|

Parent Opinions About Use of Text Messaging for Immunization Reminders

Abstract: BackgroundAdherence to childhood immunization schedules is a function of various factors. Given the increased use of technology as a strategy to increase immunization coverage, it is important to investigate how parents perceive different forms of communication, including traditional means and text-message reminders.ObjectiveTo examine current forms of communication about immunization information, parents’ satisfaction levels with these communication modes, perceived barriers and benefits to using text messagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
1
30
0
1
Order By: Relevance
“…29,30 Of the studies, 68% (n = 13) had an experimental study design, the rest were observational studies. In particular, we considered seven randomized controlled trials, 26,[31][32][33][34][35][36] five non-randomized trials, 27,30,37-39 three cross-sectional studies, 29,40,41 one case-control study, 42 and three studies that we considered to have an operational research approach. 37,43,44 Studies' sample size ranged from 50 to 9213 subjects (median = 341).…”
Section: Identified Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…29,30 Of the studies, 68% (n = 13) had an experimental study design, the rest were observational studies. In particular, we considered seven randomized controlled trials, 26,[31][32][33][34][35][36] five non-randomized trials, 27,30,37-39 three cross-sectional studies, 29,40,41 one case-control study, 42 and three studies that we considered to have an operational research approach. 37,43,44 Studies' sample size ranged from 50 to 9213 subjects (median = 341).…”
Section: Identified Studiesmentioning
confidence: 99%
“…35 Five studies focused on childhood-recommended vaccines without listing specific vaccines. 31,[40][41][42]44 Nine studies considered influenza vaccine, 26 Due to high degree of heterogeneity between studies no quantitative assessment could be performed.…”
Section: Identified Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Qualitative studies conducted in the US have also shown parents acceptability for text message immunization reminders, factors affecting mothers/caregivers' decision to vaccinate their child and benefits of receiving text for immunizations [34,35]. Further SMS text messages content were explored with parents/caregivers in order to prompt them to schedule their child's immunization appointment [36].…”
Section: Resultsmentioning
confidence: 99%